2010 IEEE International Conference on Robotics and Automation 2010
DOI: 10.1109/robot.2010.5509141
|View full text |Cite
|
Sign up to set email alerts
|

A study on wearable behavior navigation system - Development of simple parasitic humanoid system -

Abstract: Performing general human behavior by experts' navigation is expected to be realized as wearable and ubiquitous technologies and computing develop. For simple, ordinary behavior, a person does not need the assistance of an expert. However, if one is standing next to an injured/ill person, one needs the instruction on performing first aid treatment from an expert. The wearer of the wearable behavior navigation system will be able to conduct first aid treatment as an expert would. We have developed the wearable b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Several other limitations of the HMDs were perceived by users. There were concerns about the heaviness of the equipment (Oyama et al, 2010;Wang et al, 2017), the inconvenience (Rio et al, 2018) and distraction (Carbone et al, 2018). In addition, Rio et al found that the field of view available when using smart glasses was about 23°, which limited the AR visualisation area.…”
Section: Overall Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other limitations of the HMDs were perceived by users. There were concerns about the heaviness of the equipment (Oyama et al, 2010;Wang et al, 2017), the inconvenience (Rio et al, 2018) and distraction (Carbone et al, 2018). In addition, Rio et al found that the field of view available when using smart glasses was about 23°, which limited the AR visualisation area.…”
Section: Overall Systemmentioning
confidence: 99%
“…In contrast, the AR users were significantly slower in six experiments due to limitations related to the systems. This may have been due to the delay in the network, video and audio signals (Ponce, Menendez et al, 2014;Wang et al, 2017); the narrow field of view of the HMD; the distorted correspondence between the displayed view and the real view and the deteriorated sense of distance (Oyama et al, 2010;Wang et al, 2017); or the deficiencies in hand-eye coordination due to the lack of a fully transparent effect on the display (Andersen et al, 2016). A longer time could also have been experienced as participants tried to match their operative field to the absolute 3D position in which the annotation was supposed to be located (Rojas-Munoz et al, 2018).…”
Section: Task Performancementioning
confidence: 99%
“…We proposed and developed a behavior navigation system (BNS) using Augmented Reality (AR) technology and a simplified commodity-technology-based BNS using a wearable camera and fixed displays, mainly for first-aid treatment [9][10] [11].…”
Section: Behavior Navigation Systemsmentioning
confidence: 99%
“…Wearable devices are available to induce the desirable direction of human walking. Furthermore, not only the navigation of human walking, but also the navigation of general human behavior is expected to be eventually realized [7][8] [5] [9][10] [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation